The Analysis of Illocutionary Speech Act in Boris Johnson’s Speech The Fight Against COVID Is By No Means Over - Muhammad Miqdad Nuruddin (Fakultas Ilmu Budaya, 2025)
This research discuss illocutionary act in Boris Johnson’s speech entitled “The Fight Against Covid Is By No Means Over”. This speech delivered during Covid-19 pandemic, when British people faced a big challenge, whether in terms of health and social perspective. The writer is interested in analyzing how Boris Johnson use language that not only to convey information, but also to persuade, showing empathy, and building emotional bonds. This study is grounded in the theory of speech acts, originally introduced by Austin (1962) and further refined by Searle (1983), which serves as the fundamental framework. In addition, the notion of situational context, as proposed by Brown and Yule (1983), is utilized to interpret the implied meaning embedded within each utterance. This research method is qualitative with documentary technique based on document, using speech transcript that was picked from The Guardian website. From the result of analysis, it is found that there are ten utterances containing implicit meaning and related to pandemic situation. The utterances categorized to four types of illocutionary acts, namely assertives (5 data), directives (3 data), commisives (1 data), and expressives (1 data). The declaratives act was not found. The majority utterances are assertives, which shows how he indirectly conveys a fact and information to educate the public. The directives act used to warn and encourage the citizens to comply the rules, while the commisives act shows the government commitment to act decisively. Lastly, the expressive act reflecting a sense of empathy and grief towards the victim of Covid-19. In summary, his speech showed how language can be very effective in a crucial situation. Through word choice, which is full of meaning and proper context, he can convey an informative but also emotional and persuasive message. This research indicates that the speech act analysis can help us comprehend the deeper meaning of the speech, especially in a political context and public policy.
Reupload Repository Maya 25 Maret 2026
Keywords: Covid; Pandemic